The Visualizations Methods of Geometrical Forms in teaching of Civil Engineering Students (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Development of spatial representation (the ability to imagine three-dimensional objects using flat pictures or drawings), skills of the intuitive decision of spatial problems and more meaningful use of CAD software are essential for qualified education of students. Visualization of geometric problems helps students to understand and to solve the given geometric tasks. The paper describes types of visualization of geometrical objects from graphic exercises of compulsory subject “Civil EngineeringGraphics”. This course is specified for Civil engineering undergraduate 2nd year students of Riga Technical university.Performance of a breadboard model, creation of the given model using ArchiCAD and using augmented reality (AR) software are included in the course "Civil Engineering Graphics” assignments. The examples of the tasks of 3D modeling in learning process are presented in this article. AR application allows faster understanding of complicated spatial problems and relationships and was used to entertain the students during the studies. Before mentioned approach was enabled to develop spatial skills of students, facilitate the students to obtain more practical experience in solving graphic exercises and was supposed enhance the quality of graphic education.